Do social media influencers shape halal purchase intentions among Gen Z? - Salsabilla, Dewi Insyirahti; Susminingsih, Susminingsih; Fakhrina, Agus; Adinugraha, Hendri Hermawan (Asian Journal of Islamic Management (AJIM), 2026)
Purpose – This study aims to describe the influence of influencers on Gen Z in halal purchase intention, especially in Gen Z in cities with high socio-religiosity, and to test whether religiosity is able to moderate the attitudes of influencers in their role as mediators.Methodology – This study employs a quantitative approach using structural equation modeling–partial least squares (SEM-PLS) with SmartPLS 4.0, based on data collected from 262 Gen Z respondents in Pekalongan, a city characterized by strong socio-religious values. Drawing on the theory of planned behavior (TPB), the model integrates trust, subjective norms, perceived behavioral control, credibility, attitude, and religiosity to explain halal purchase intention in a social media environment.Findings – The results reveal that attitude is the strongest predictor of halal purchase intention. Trust, subjective norms, and perceived behavioral control significantly and positively influence attitude, although their effect sizes are relatively weak. In contrast, credibility does not significantly affect attitude. Attitude significantly mediates the relationship between influencer-related factors and purchase intention. Religiosity, however, neither directly influences purchase intention nor moderates the relationship between attitude and purchase intention.Implications – These findings suggest that marketers should focus on strengthening positive consumer attitudes through trust-building, social endorsement, and perceived consumer control, rather than relying solely on influencer credibility or religiosity cues.Originality – This study extends halal consumption literature by integrating religiosity and attitude within the TPB framework and provides empirical evidence on influencer-driven halal purchase behavior among Gen Z in a highly religious social context.